Does Terrorism Work? - Eric D. Gould; Esteban F. Klor (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper examines whether terrorism is an effective tool to achieve political goals. By exploiting variation in terror attacks over time and across locations in Israel from 1984 to 2006, we show that local terror attacks cause Israelis to be: (i) more willing to grant territorial concessions to the Palestinians; (ii) more willing to accept a Palestinian state; (iii) less likely to identify oneself as being right-wing; and (iv) more likely to have a favorable opinion of Arabs. These effects are especially pronounced for individuals from particular demographic groups which are typically right-wing in their political views. In addition, we show that terror induces Israelis to vote increasingly for right-wing parties. This pattern of results demonstrates that right-wing parties are becoming more accommodating to Palestinian demands for territorial concessions. Hence, this paper shows that terrorism appears to be an effective strategy in terms of shifting the entire Israeli political landscape to the left. These findings may shed light on the causes underlying the spread of global terrorism in the last few decades.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330